2013
DOI: 10.1016/j.virol.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

A partial deletion in non-structural protein 3A can attenuate foot-and-mouth disease virus in cattle

Abstract: The role of non-structural protein 3A of foot-and-mouth disease virus (FMDV) on the virulence in cattle has received significant attention. Particularly, a characteristic 10-20 amino acid deletion has been implicated as responsible for virus attenuation in cattle: a 10 amino acid deletion in the naturally occurring, porcinophilic FMDV O1 Taiwanese strain, and an approximately 20 amino acid deletion found in egg-adapted derivatives of FMDV serotypes O1 and C3. Previous reports using chimeric viruses linked the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 37 publications
3
44
0
Order By: Relevance
“…Interestingly, O1C3A-PLDGv, replicated at a rate similar to the parental virus in FPK cells (data not shown). A similar replication pattern is observed with FMDV O/TAW/97 (28) and with a recently reported recombinant FMDV O1Cv virus harboring a deletion in 3A between residues 87 to 106 (therefore lacking the DCTN3 binding site) (12). Perhaps binding between FMDV 3A and host DCTN3 may contribute to the host range specificity of the virus.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Interestingly, O1C3A-PLDGv, replicated at a rate similar to the parental virus in FPK cells (data not shown). A similar replication pattern is observed with FMDV O/TAW/97 (28) and with a recently reported recombinant FMDV O1Cv virus harboring a deletion in 3A between residues 87 to 106 (therefore lacking the DCTN3 binding site) (12). Perhaps binding between FMDV 3A and host DCTN3 may contribute to the host range specificity of the virus.…”
Section: Discussionsupporting
confidence: 86%
“…The results demonstrated that viruses O1Cv and O1C3A-PLDGv both produced a similar large plaque size in LFBK-␣V␤6 cells. However, while virus O1Cv produced smaller plaques in FBK cells than those produced in LFBK-␣V␤6 cells, virus O1C3A-PLDGv was completely unable to produce any visible plaques, similarly to what has been previously described in O/TAW/97 (12). Thus, the substitution in 3A harbored by O1C3A-PLDGv virus undermined its ability of the virus to replicate in primary bovine cell cultures.…”
Section: Identification Of the Dctn3 Binding Site On Fmdv 3asupporting
confidence: 65%
See 2 more Smart Citations
“…32 Variants of FMDV with deletions within the 3A protein have been identified; these are associated with more restricted host range of the virus including attenuation in cattle. 34 As indicated above, the 3C protein is a chymotrypsin-like protease and is responsible for most of the proteolytic cleavages within the virus encoded polyprotein (see Figure 2). In contrast to poliovirus (PV) and other enteroviruses, which require 3CD as the active protease for P1 processing, the FMDV 3C…”
mentioning
confidence: 99%